Robust sliding mode control for the MMC‐HVDC transmission system with SCR uncertainty - Farzin Gharaghani; Mehdi Asadi (IET Power Electronics)
Abstract Modular multilevel green converter based high voltage direct current (MMC‐HVDC) transmission system has become a practical solution to interconnect renewable energy sources to main AC grids. Connecting the MMC to a weak AC system is still a challengeable problem. This paper proposes a sliding mode control‐based method for the MMC. By considering short circuit ratio parameter of the AC grid as uncertainty, a suitable mathematical model is developed. Also, relations among control parameters and their validity conditions are obtained. The proposed control scheme has faster dynamic responses to uncertainty and external disturbances compared to the conventional vector current control method with proportional–integral controller. At last, simulation results in the MATLAB/SIMULINK software environment are presented that the proposed control scheme is effective.